PREVALENCE AND ASSOCIATED FACTORS OF COMMON MENTAL HEALTH PROBLEMS AND UTILIZATION OF MENTAL HEALTH SERVICES AMONG PEOPLE LIVING WITH HIV/AIDS IN UNIVERSITY OF GONDAR COMPRESSIVE SPECIALIZED HOSPITAL, ETHIOPIA - HIWOT ENKU SELAMAWI; SEID HASSEN HUSSIEN; ABEBE FEKADU ADERA; DESSALEW SHEFERAW YESUF (Innovare Journal of Social Sciences, 2025)
Mental health problems in this thesis refer to a wide range of mental conditions, ranging from self-reported symptoms such as worries and mildly depressed mood to symptoms that meet the criteria for a diagnosis. This study was conducted in Gondar University Hospital, using quantitative method to achieve the objective of research. And, hence, quantitative survey study design was applied; data were collected from a total of 357 participants selected from antiretroviral service users using simple random sampling technique. Self-reporting questionnaire was used to collect data. Descriptive statistics was employed to show the frequency and distribution of sociodemographic characteristics of the study participant. Binary logistic regression model was used to identify association between dependent (Prevalence of common mental health problems) and independent variables (Sociodemographic, clinical and mental health service utilization). The result revealed that the prevalence of common mental health problem among people living with HIV/acquired immunodeficiency syndrome (AIDS) attending antiretroviral therapy in the study setting was 32.77% from 357 study participants. In the multivariable logistic regression model occupation, the presence of antiretroviral drug side effect and lack of social support were statistically associated with common mental health problems among people living with HIV/AIDS attending ART at University of Gondar Compressive specialized hospital. Regarding mental health service utilization, only 60 (16.8%) of the study participant were utilizing the mental health service in the hospital. In this study, the prevalence of common mental health problem was high but mental health service utilization was low. In this study, about one-third (32.77%) of people living HIV reported that having mental health problem. This shows that the prevalence of common mental health problem among people living with HIV in University of Gondar comprehensive specialized hospital is high. Beside this utilization of mental health service among this group of people is low which 16.8%. Being unemployed, the presence of antiretroviral drug side effect and having social support were independent predictors of common mental health problem among HIV-positive adult patients attending ART follow-up at the University of Gondar compressive specialized hospital. However, utilization of mental health service among these groups of population is low compared with its prevalence. Therefore, further researcher and interventions are need for prevention and control of common mental health disorder (CMD) among people living with HIV. Especial attention, care, and support are mandatory for those HIV-positive people having ART drug side effect and unemployed. Strengthen and improve social support have good effect in the reduction of CMD among people living with HIV.